PENGARUH DIVERSIFIKASI PROGRAM STUDI TERHADAP MINAT KULIAH MAHASISWA PADA UNIVERSITAS ISLAM NEGERI ALAUDDIN MAKASSAR - Ahmad Efendi (Universitas Islam Negeri Alauddin, 2018)
The aims of this research isto test and to analyze theeffect ofdiversified coursesto the college student’s interest.This study usesprimary datathrough asurvey of364college student’sas sampleof allstudents of the facultyof Sharia, the faculty of Sciences and Technologyand the faculty of Health Sciences. The survey was conducted from October to November2012.Data were analyzed using regression methods by Statistical Program for SocialScience(SPSS).The results showed thatbrand imagehas apositiveand significanteffectto the college student’s interest. Considering theresults,theAlauddinIslamic State Universitymust continueto innovatein the form ofa diversifiedprogram of studyin order to competewith competitors.